A holistic perspective on the French building and construction GHG footprint. Issue 1 (1st September 2022) - Pellan, M; Louërat, M; El Beze, J; Habert, G
Abstract: In order to deliver on the Paris agreement, the decarbonisation of the building sector is critical. An accurate assessment of its life cycle GHG emissions is essential to identify emissions hotspots and decarbonisation potentials in order to prepare future policies such as sectoral carbon budgets. However, today a lack of common GHG emissions accounting exists between climate policies and building environmental assessment. The first one relies on the production-based accounting system of national inventories, while the second one takes a life cycle approach, thus accounting for cross-sectoral emissions. As a result, at national level, there is no holistic assessment of the building and construction GHG footprint, which is detrimental to prepare decarbonisation pathways. This research aims to characterise the life cycle emissions of the sector, taking the French case as an example. A thorough analysis of operational direct and indirect emissions as well as embodied emissions allows the identification of emissions hotspots, both at sectoral and geographical levels. The methodology enables an integrated cross-sectoral perspective that is essential for national assessments and future policy interventions. Results show operational emissions represent 65% of the sector GHG footprint. Embodied emissions are mainly due to industry and energy upstream emissions, with roughly 60% imported from abroad. The results can help to identify main decarbonisation levers to reach net-zero emissions by 2050.